Security assessment of four open source software systems - Faraz Idris Khan; Yasir Javed; Mamdouh Alenezi (Institute of Advanced Engineering and Science, 2019)
Incorporating Open Source Software (OSS) tools in software development is increasing day by day due to their accessibility on the internet. With the advantages of OSS comes disadvantages in terms of security vulnerabilities. Therefore, in this paper, we analyzed four famous open source software tools (i.e. Moodle, Joomla, Flask and VLC media player) which are used by software developers nowadays. For the analysis of each system, security vulnerabilities and weakness were identified, threat models were modeled,and code inspection was performed. The findings are discussed in more details.